Internal structure of the Kutno end moraine (Kłodawa Plateau, central Poland): contributions from documentation of former mining excavations - Roman, Małgorzata (Acta Geographica Lodziensia, 2024)
The Kutno moraine is the most clearly expressed end-moraine ridge from the recession of the Warta ice sheet (Late Saalian) of the Odra Glaciation (MIS 6) in the relief of Central Poland. Its formation has been interpreted in various ways: a typical accumulative end-moraine, a glaciotectonically controlled form, and also as relicts of ice-moraine ridges. To supplement the knowledge about the structure of the moraine ridge in its highest, central part, previously unpublished photographic materials of outcrops and lithofacies studies of sediments from 2003–2005 and 2017 were presented that document the walls of now-defunct gravel pits. It was found that the moraines are composed of sediments indicative for the proximal parts of glac-imarginal fans formed as a result of sheet floods, grain flows and cohesive debris flows. The contribution of compressive deformations related to the pressure of the ice sheet is negligible, and sediment disturbances are mainly caused by gravity flows and subsidence. It was found that the end moraines of Kutno have an accumulative nature.